Durability of Residual Strength on Ac-Wc Mixture Using Bottom Ash As Fine Aggregate Substitution - Irianto, Irianto; Mabui, Didik S.S; Sila, Ardi Azis (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. This study aims to determine the durability of the residual strength in the Asphalt Concrete – Wearing Course (AC-WC) mixture that uses bottom ash waste as a substitute for fine aggregate. The Marshall Test revealed that the stability value of all variations of the tested immersion met the minimum standard, which was greater than 800 kg, namely for the 0 hour immersion variation of 2170.75 kg, the 24-hour immersion variation of 2014, 62 kg, the immersion variation 48 hours of 1938.07 kg, variation of immersion 96 hours of 1853.45 kg, and the variation of immersion 168 hours of stability value obtained is 1747.68 kg. And for the residual strength index in the 24-hour immersion variation the residual stability index was obtained at 92.81%, for the 48-hour immersion variation the residual stability index was obtained at 89.33%, while for the 96-hour immersion variation the residual stability index was obtained at 85.38%. and for the variation of immersion 168 hours residual stability index was obtained at 80.51%, so that which meets the standard of at least 90% is the 24-hour variation.